Successive reduction for preparation of various PdxPty-MWCNTs catalysts for formic acid oxidation - Pitak Wongthep (2018)
© 2016, Chiang Mai University. All rights reserved. The development of catalysts for fuel cell electrode is our approach. Platinum (Pt) and palladium (Pd) were used to prepare various PdxPty catalysts by reduction method to study their electrocatalytic activities of the formic acid oxidation reaction. The support used multi-walled carbon nanotubes (MWCNTs) was functionalized by mixed solution of HNO3 and H2SO4 to promote oxygen-containing functional groups and then further load the catalyst nanoparticles onto that functionalized MWCNT surface. The functionalized MWCNTs were characterized their functional groups by Fourier transform infrared spectroscopy (FT-IR) while X-ray diffraction (XRD) was used to probing of the prepared catalyst compositions. The prepared PdxPty-MWCNT catalyst electrodes were studied in electrooxidation of formic acid by cyclic voltammetry (CV) and chronoamperometry (CA). The prepared PdxPty-MWCNT catalysts results show excellent activities and stabilities for the formic acid electrooxidation indicated by their lower onset potential and higher current density peak. Incorporation of Pt and Pd on the functionalized MWCNTs matrix enhances the electrochemical active surface area to achieve the catalytic oxidation reactions.